(untitled) (Nigerian Dental Journal, 2012)
Objective: To determine the age at referral for first orthodontic consultation at the University College Hospital Ibadan, Nigeria. Method: A retrospective audit study carried out between January 01 and December 30, 2009 at the Orthodontic Unit of the University College Hospital Ibadan, Nigeria. Data for patients diagnosed with at least one form of malocclusion were retrieved from the patients record held by the unit. Patients whose initial orthodontic consultation was between January 01, 2009 and December 30, 2009 were included. The age of each patient at referral was calculated using the patient’s date of birth. Result: A total of 103 patients attended the clinic during the period of study. The patients’ age ranged from 6 to 44 years. The mean age at referral was 13.3±1.2 years. Only 4.0% of the patients were referred in the early mixed dentition stage between 7and 9 years, 96.0% of patients were referred at either the primary or early permanent dentition stage. Conclusion: Majority of patients seen at the orthodontic clinic of the University College Hospital Ibadan, were not referred at the appropriate age for their first orthodontic consultation.